The association between use of chemsex drugs and HIV clinic attendance among gay and bisexual men living with HIV in London. Issue 8 (5th May 2021) - Howarth, AR; Apea, V; Michie, S; Morris, S; Sachikonye, M; Mercer, CH; Evans, A; Delpech, VC; Sabin, C; Burns, FM
Abstract : Objectives: To investigate the association between chemsex drug use and HIV clinic attendance among gay and bisexual men in London. Methods: A cross‐sectional survey of adults (> 18 years) diagnosed with HIV for > 4 months, attending seven London HIV clinics (May 2014 to August 2015). Participants self‐completed an anonymous questionnaire linked to clinical data. Sub‐optimal clinic attenders had missed one or more HIV clinic appointments in the past year, or had a history of non‐attendance for > 1 year. Results: Over half (56%) of the 570 men who identified as gay or bisexual reported taking recreational drugs in the past 5 years and 71.5% of these men had used chemsex drugs in the past year. Among men reporting chemsex drug use (past year), 32.1% had injected any drugs in the past year. Sub‐optimal clinic attenders were more likely than regular attenders to report chemsex drug use (past year; 46.9% vs . 33.2%, P = 0.001), injecting any drugs (past year; 17.1% vs . 8.9%, P = 0.011) and recreational drug use (past 5 years; 65.5% vs . 48.8%, P < 0.001). One in five sub‐optimal attenders had missed an HIV clinic appointment because of taking recreational drugs (17.4% vs . 1.8%, P < 0.001). In multivariable logistic regression, chemsex drug use was significantly associated with sub‐optimal clinic attendance (adjusted odds ratio = 1.71, 95% confidence interval: 1.10–2.65, P = 0.02). Conclusions: Our findings highlight the importance of systematic assessment of drug use and development of tools to aid routine assessment. We suggest that chemsex drug use should be addressed when developing interventions to improve engagement in HIV care among gay and bisexual men.